Performa dan Kecernaan Protein Kasar Ayam Sensi-1 Agrinak dengan Level Protein Ransum yang Berbeda - Rudi Prasetyo Hantoro, Franciscus (Jurnal Ilmu dan Industri Peternakan, 2023)
The study aimed to determine the performance and digestibility of crude protein of Sensi-1 Agrinak chickens with different feed protein levels. The research was conducted from March to May 2022 at Assessment Institute for Agricultural Technology of Central Java. The material used was 120 SenSi-1 Agrinak chickens. The feed used in the study consisted of rice bran, DDGS, yellow corn, cassava flour, wheat bran, MBM, fish meal, minerals, DL-Methionone, Trypthopan, threonine, and L-Lysine. The study was conducted during one maintenance period of 70 days. In the starter phase (1-28 days), DOC is kept together in colony cages with commercial feed. In the grower phase (29-70 days), chickens are put into a treatment unit based on uniform body weight in a stage pan cage measuring 1 x 1 x 70 meters, as many as 12 cages filled with ten chickens (unsexing). The research method uses the Group Random Design (RAK) method. Consists of three treatments, namely T1 (CP = 14.44%), T2 (CP = 16.05%), and T3 (CP = 18.00%), with four treatment groups as replications. Data used variance analysis. The results showed that giving different protein levels to Sensi-1 Agrinak chickens obtained the same results on consumption, weight gain, feed conversion, and protein digestibility but significantly different from IOFC, protein consumption, and N retention.